TRENDS AND PATTERNS IN ONLINE PURCHASE DECISION RESEARCH A LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Sulistyowati, Tussi (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
Abstract : The internet has transformed the way consumers make purchase decisions, and with the increasing popularity of e-commerce, it has become vital to understand the factors that influence online purchase decisions. The COVID-19 pandemic has further accelerated the shift towards online shopping, making it even more crucial to understand the online purchase decision-making process. This bibliometric review examines 95 articles on the keyword